Household survey for evaluation of Lebanon women's empowerment project, 2014 (UK Data Service, 2020)
The Household Survey for Evaluation of Lebanon Women's Empowerment Project, 2014 data were collected by Oxfam GB as part of the organisation’s Global Performance Framework. Under this framework, a small number of completed or mature projects are selected at random each year for an evaluation of their impact, known as an Effectiveness Review. The data were used to evaluate the impact of the "Women's Access to Justice in the MENA Region" project, which took place in Lebanon between January 2013 and July 2014. The project aimed to improve the status and lives of women and girls in the Middle East and North Africa (MENA) region, by enhancing the quality of legal services for poor and vulnerable women. The project was implemented on four levels of intervention: individual, community, institutional, and policy. At the individual level, participants engaged in awareness-raising sessions to share knowledge on women's rights, and the project provided lawyers free of charge. At the community level, the project identified community leaders as actors of change, who also received training and participated in awareness-raising sessions. Institutionally, the project worked with lawyers and courts to create a better environment for women to access the judicial system. The data collection took place during December 2014 in four regions: the El Metn region, where communities had been involved in the project, and three other communities which served as the control for the evaluation. Oxfam employed a quasi-experimental approach for the evaluation, matching participants of the program with women from the control communities who were similar in a range of characteristics. In total, data were collected from 675, of which 225 had participated in the project.